THE RELATIONSHIP OF READING INTEREST AND CONFIDENCE IN ELEMENTARY SCHOOL STUDENTS' ENGLISH LITERACY ABILITIES - Anisa Marhayani (Esteem Journal of English Education Study Programme, 2024)
This thesis discusses the relationship between interest in reading and self-confidence towards the literacy abilities of elementary school students. This research aims to determine the relationship between interest in reading and self-confidence on the English literacy skills of elementary school students. This type of research is correlational research using quantitative methodology, the subjects of this research are class IV students at SD Negeri 231 Palembang, the sample is class IV.C. The results of the research were multiple correlation regression tests to obtain how big the relationship between independence (interest reading and self-confidence) on the dependent variable (English literacy ability) elementary school students who are at a very strong level because they obtained a score of 0.882. Then the F test of the hypothesis shows that H0 is rejected and Ha is accepted because the calculated F hypothesis = 25.975 > F table = 3.385 and the significant value is 0.000 < 0.05. The magnitude of the contribution between interest in reading and self-confidence on the English literacy skills of elementary school students using the determinant coefficient test obtained a result of 67.5%, while the rest was influenced by other factors.